Analysis of French grammatical gender errors committed by learners in Tanzanian universities - Manyasa, Jonace (Vestnik za tuje jezike, 2019)
This paper analyses the grammatical gender errors committed by learners of French as a foreign language in four Tanzanian universities: UDSM, UDOM, DUCE and Makumira (University of Dar es Salaam, University of Dodoma, Dar es Salaam University College of Education and Maku-mira University). The paper has three specific objectives: (i) to identify grammatical gender errors, (ii) to account for their sources and (iii) to propose a corrective treatment. The study included a to-tal of 61 respondents. The data was collected through learners' written texts in French from which a corpus was developed. The study was guided by the error analysis approach and interlanguage theory. The data was analysed qualitatively and quantitatively. The findings show that grammati-cal gender errors were found with regard to the masculine definite article (29.73%), the feminine definite article (24.32%), the masculine indefinite article (22.97%), the feminine indefinite article (16.22%) and possessive adjectives (6.76%). These findings show there is a need to help learners of French as a foreign language in the context of Tanzania using the recommended strategies.
Keywords: analiza napak; francoščina; napake (jezik); slovnični spol; študenti; Tanzanija; tuji jeziki